FAKTOR PENENTU PERILAKU ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN SURAT KABAR HARIAN KEDAULATAN RAKYAT - Saputra , Indra Sandra; Nugroho , Muhammad Awal Satrio; Wikaningtyas , Suci Utami (Jurnal Riset Manajemen Akuntansi Indonesia, 2025)
This study aims to determine the effect of organizational commitment, organizational justice, job satisfaction, transformational leadership and transactional leadership partially on employee Organizational Citizenship Behavior and to determine the effect of organizational commitment, organizational justice, job satisfaction, transformational leadership and transactional leadership simultaneously on employee Organizational Citizenship Behavior. The population taken in this study were all employees of the Kedaulatan Rakyat Daily Newspaper. In this study, the research sample was permanent employees of the Kedaulatan Rakyat Daily Newspaper. The sampling technique used the proportional random sampling method, namely the technique of taking samples randomly from each population and then the number of samples taken from each population was determined randomly with a sample of 110 employees selected randomly. The analysis tool used was multiple linear regression analysis. Based on the results of the analysis, it can be concluded that there is a significant influence of organizational commitment, organizational justice, job satisfaction and transformational leadership on employee Organizational Citizenship Behavior, but there is no significant influence between Transactional Leadership and Organizational Citizenship Behavior. Simultaneous testing obtained results that there is an influence of organizational commitment, organizational justice, job satisfaction, transformational leadership and transactional leadership on employee Organizational Citizenship Behavior.